Preparation method and application of sulfur-cadmium-zinc quantum dot / mesoporous silica composite photocatalyst

Synthesizing cadmium sulfide zinc quantum dot/mesporous silica composite photocatalysts through hydrothermal method and thermal injection method, solving the problems of low surface porosity of quantum dots and lack of photocatalytic activity of mesporous silica, achieving efficient CO2 Photocatalytic reduction, catalytic activity is significantly improved and remains stable for a long time.

CN119236971AActive Publication Date: 2025-01-03JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411400268.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing zero-dimensional quantum dot photocatalysts are difficult to capture CO2 and reaction intermediates due to their low surface porosity during CO2 reduction, which limits the improvement of catalytic performance. Mesoporous silica itself lacks photocatalytic activity and cannot be alone. Convert CO2 into renewable fuel.

Method used

Hydrothermal method and thermal injection method are used to synthesize the composite photocatalyst of cadmium sulfide and zinc quantum dots/mesoporous silica. The surface activity of the quantum dots is enhanced by MUA modification, and combined with mesoporous silica to form a catalyst with a high specific surface area. Improve photocatalytic activity.

Benefits of technology

The photocatalytic reduction efficiency of CO2 was significantly improved, the photocatalytic activity of the composite material reached 898.6 μmol g-1h-1, and the catalytic stability was maintained in 20-hour cycle experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236971A_ABST
    Figure CN119236971A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis, and discloses a preparation method and application of a sulfur-cadmium-zinc quantum dot / mesoporous silica composite photocatalyst. The preparation method comprises the following steps: (1) preparing mesoporous silica (mesop-SiO2); (2) preparing sulfur-cadmium-zinc quantum dots (ZnCdS QDs); (3) preparing MUA modified sulfur-cadmium-zinc quantum dots; and (4) compounding the sulfur-cadmium-zinc quantum dots and mesoporous silica according to a ratio to obtain the sulfur-cadmium-zinc quantum dot / mesoporous silica (MUA-ZnCdS QDs / mesop-SiO2) composite photocatalyst. According to the prepared sulfur-cadmium-zinc quantum dot / mesoporous silica composite photocatalyst, the advantage that the mesoporous silica can capture CO2 due to the high specific area and the advantage that the sulfur-cadmium-zinc quantum dots have proper energy band positions are utilized, and efficient conversion of CO2 is achieved. The method is easy and convenient to operate, and the purpose of converting CO2 into renewable fuel is effectively achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis and relates to a preparation method and application of a sulfur-cadmium zinc quantum dot / mesoporous silicon dioxide composite photocatalyst. Background Art

[0002] With the growth of global population and rapid economic development, human consumption of fossil fuels such as coal, oil and natural gas has increased dramatically, causing serious environmental pollution and energy crisis. Excessive emission of greenhouse gases has led to global warming. At present, the global CO 2 Concentrations have reached 420 ppm, forcing the world to look for ways to reduce CO 2 It is an effective means to convert greenhouse gases such as CO into renewable energy. 2 Capturing and converting it into usable high-value compounds has become a key approach to reducing CO 2 Among them, the main developed methods are electrochemical catalysis, thermochemical catalysis, biocatalysis and photochemical catalysis. Photochemical catalysis is widely used in the conversion of CO due to its advantages of high efficiency, environmental protection, simple operation and low cost. 2 .

[0003] Researchers have found that zero-dimensional quantum dots (QDs) materials have been widely studied as building blocks for photocatalysts due to their special quantum size effect, electron transfer properties, and efficient absorption of visible light. Ternary ZnCdS has a high absorption coefficient, which creates good conditions for adjusting the optical properties from the ultraviolet to the visible light range and can adjust the appropriate band gap range. 2 In the field of ZnCdS QDs, high catalytic activity is shown; however, due to the low porosity of the QD surface, it is difficult to capture CO 2 and reaction intermediates, which greatly limits the improvement of quantum dot catalytic performance. Therefore, a high specific surface area and efficient capture of CO 2 Catalyst supports for enhancing the photoreduction of CO by quantum dots 2 The catalytic activity has positive significance.

[0004] In recent years, mesoporous silica nanoparticles (mesop-SiO 2 ) has become a hot topic in the catalytic field due to its large open pore structure, high specific surface area, excellent solvent dispersibility, and good biocompatibility. The above advantages make mesoporous silica very important in achieving CO 2 Good progress has been made in the capture and catalytic conversion of CO. However, mesoporous silica itself has no photocatalytic activity and cannot convert CO 2Therefore, by combining zinc cadmium sulfur quantum dots (ZnCdS QDs) and mesoporous silica (mesop-SiO 2 ) combined to form a composite photocatalyst for efficient photoreduction of CO 2 The strategy is feasible. No relevant reports have been seen so far. Summary of the invention

[0005] The present invention uses hydrothermal method and hot injection method to prepare sulfur cadmium zinc quantum dots / mesoporous silica composite photocatalyst for efficient photocatalytic conversion of CO 2 The photocatalytic activity is greatly improved by converting it into CO, which has good practical application value. A method for preparing a sulfur cadmium zinc quantum dot / mesoporous silica composite photocatalyst comprises the following steps:

[0006] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0007] Dissolve hexadecyltrimethylammonium bromide (CTAB) and butyraldehyde in water, pour into a sealed bottle, stir at room temperature for 5-10 minutes, quickly add ammonia water, stir for 30-60 minutes, then add tetraethyl silicate (TEOS), stir at room temperature for 12-24 hours, centrifuge and dry the product, and finally calcine in air atmosphere;

[0008] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0009] First, sulfur powder was added to octadecene ODE in N 2 The precursor S is prepared by heating until it dissolves; then, cadmium oxide CdO and zinc acetate Zn(OAc) are added. 2 Add to the mixture of octadecene ODE and oleic acid OA, then in N 2 The ZnCd precursor is prepared by heating the precursor until it is dissolved; finally, the S precursor is injected into the ZnCd precursor, cooled to room temperature, and the obtained sulfur cadmium zinc quantum dots are precipitated with acetone and then dispersed in n-hexane;

[0010] (3) MUA-modified zinc cadmium sulfate quantum dots

[0011] Dissolve 11-mercaptoundecanoic acid MUA in methanol, and adjust the pH of the solution to 9-12 with tetramethylammonium hydroxide pentahydrate to obtain a MUA mixed solution;

[0012] In the dark, the zinc cadmium sulfur quantum dots ZnCdS QDs obtained in step (2) were dispersed in the MUA mixture and the container was placed in N 2 The mixture was heated under reflux at 60-80 °C overnight under flow, precipitated with ethyl acetate and diethyl ether, washed with acetone and dispersed in water, and recorded as MUA-ZnCdS QDs.

[0013] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica composite photocatalyst

[0014] The MUA-ZnCdS QDs obtained in step (3) and the mesoporous silica mesop-SiO 2 Disperse in deionized water, stir in dark for 12-24 hours, and obtain zinc cadmium sulfate quantum dots / mesoporous silica composite photocatalyst, denoted as MUA-ZnCdS QDs / mesop-SiO 2 .

[0015] In step (1), the dosage ratio of hexadecyltrimethylammonium bromide, butyraldehyde, ammonia water and tetraethyl silicate is 0.64g:15.0mL:6.0mL:2.8mL; wherein the concentration of ammonia water is 25-28wt%.

[0016] The calcination temperature is 550°C and the calcination time is 6h.

[0017] In step (2), sulfur powder, CdO and Zn(OAc) 2 The molar ratio of octadecene ODE and oleic acid OA is 2:1:1; in the mixture of octadecene ODE and oleic acid OA, the volume ratio of ODE:OA is 13:6;

[0018] In step (3), the mass ratio of MUA and ZnCdS QDs is 1:1;

[0019] In step (4), MUA-ZnCdS QDs and mesoporous silica (mesop-SiO 2 )'s mass ratio is 1:1.7-19.

[0020] The prepared zinc cadmium sulfate quantum dots / mesoporous silica (MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 For the use of CO.

[0021] The above technical analysis test method is specifically as follows:

[0022] (1) The photocatalytic performance of different photocatalysts was tested in a quartz glass reactor. The generated CO was analyzed using a gas chromatograph. The specific experimental steps are as follows: 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was used to pass through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0023] (2) The light source uses a light power density of 1000mW cm -2 300W Xe lamp. Analysis was performed every 60 minutes.

[0024] Technical advantages of the present invention

[0025] (1) The present invention synthesizes the photocatalytic composite material by using a hydrothermal method and a hot injection method. The synthesis method makes the mesoporous silica material have a uniform distribution of mesopores, and the quantum dots are highly dispersed and uniform in size. Moreover, after the quantum dots are exchanged with the ligand MUA, the surface has a more reactive surface group, which can be evenly dispersed in an aqueous solution and is conducive to compounding with the mesoporous silica.

[0026] (2) The photocatalytic composite material prepared by the present invention achieves efficient photoreduction of CO 2 The photocatalytic activity of the composite material reached 898.6 μmol g -1 h -1 .

[0027] (3) The photocatalytic composite material prepared by the present invention has a high catalytic stability and still has 91% catalytic activity after a 20-hour cycle test. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The nitrogen adsorption / emission spectra (BET) of Examples 1-5 are shown;

[0029] Figure 2 This is a morphology characterization diagram of the composite photocatalyst obtained in Example 5;

[0030] Figure 3 The photocatalytic reduction of CO by the composite photocatalyst obtained in Example 1-5 2 Performance test chart;

[0031] Figure 4 This is a photocatalytic cycle test of the composite photocatalyst obtained in Example 5. DETAILED DESCRIPTION

[0032] The technology of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0033] Example 1

[0034] A kind of zinc cadmium sulfate quantum dots / mesoporous silica (5% MUA-ZnCdS QDs / mesop-SiO 2 ) The method for preparing the composite photocatalyst comprises the following steps:

[0035] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0036] 0.64 g of hexadecyltrimethylammonium bromide (CTAB), 12.0 mL of deionized water and 15.0 mL of butyraldehyde were mixed in a sealed bottle and stirred at 27°C for 5 min. 6.0 mL of ammonia (25-28 wt%) was quickly added and stirred for 30 min. Then 2.8 mL of tetraethyl silicate (TEOS) was added and stirred at 27°C for 24 h. The product was filtered, washed, dried at 100°C for 12 h, and finally calcined in air at 550°C for 6 h.

[0037] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0038] First, 0.51 g of sulfur powder was added to 16 ml of octadecene (ODE) under N 2 The precursor was prepared by heating to 150°C until dissolved; then, 0.256 g of cadmium oxide (CdO) and 0.368 g of zinc acetate (Zn(OAc) 2 ) was added to a mixture of 13 ml of octadecene (ODE) and 6 ml of oleic acid (OA), and then heated to N 2 The ZnCd precursor was prepared by heating to 300°C until dissolved; finally, 4 ml of the S precursor was injected into the ZnCd precursor for 10 minutes. After cooling to room temperature, the quantum dots were precipitated with acetone and then dispersed in n-hexane.

[0039] (3) MUA-modified zinc cadmium sulfate quantum dots

[0040] 20 mg of 11-mercaptoundecanoic acid (MUA) was placed in a reaction vessel, 15 ml of methanol (11.85 g) was added, and the pH was adjusted to greater than 10 with tetramethylammonium hydroxide pentahydrate. 20 mg of zinc cadmium sulfate quantum dots (ZnCdSQDs) were dispersed in the mixture under dark conditions, and the vessel was placed under N 2 The mixture was heated under reflux at 60°C overnight. The quantum dots were precipitated with ethyl acetate and ether, washed with acetone and dispersed in water, and were recorded as MUA-ZnCdS QDs.

[0041] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica (5% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst

[0042] 5 mg of zinc cadmium sulfate quantum dots (MUA-ZnCdS QDs) and 95 mg of mesoporous silica (mesop-SiO 2 ) were dispersed in 10 ml of deionized water and stirred for 24 hours in a dark environment to obtain 5% MUA-ZnCdSQDs / mesoporous silica. 2 ) composite photocatalyst.

[0043] (5) 5% MUA-ZnCdS QDs / mesoporous silica 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 experiment.

[0044] 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was passed through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0045] Depend on Figure 1 The specific surface area is calculated to be 232.4 m 2 g -1 .Depend on Figure 3 It can be seen that the production rate of CO is 325.7 μmol g -1 h -1 .

[0046] Example 2

[0047] A kind of zinc cadmium sulfate quantum dots / mesoporous silica (10% MUA-ZnCdS QDs / mesop-SiO 2 ) The method for preparing the composite photocatalyst comprises the following steps:

[0048] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0049] 0.64 g of hexadecyltrimethylammonium bromide (CTAB), 12.0 mL of deionized water and 15.0 mL of butyraldehyde were mixed in a sealed bottle and stirred at 27°C for 5 min. 6.0 mL of ammonia (25-28 wt%) was quickly added and stirred for 30 min. Then 2.8 mL of tetraethyl silicate (TEOS) was added and stirred at 27°C for 24 h. The product was filtered, washed, dried at 100°C for 12 h, and finally calcined in air at 550°C for 6 h.

[0050] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0051] First, 0.51 g of sulfur powder was added to 16 ml of octadecene (ODE) under N 2 The precursor was prepared by heating to 150°C until dissolved; then, 0.256 g of cadmium oxide (CdO) and 0.368 g of zinc acetate (Zn(OAc) 2) was added to a mixture of 13 ml of octadecene (ODE) and 6 ml of oleic acid (OA), and then heated to N 2 The ZnCd precursor was prepared by heating to 300°C until dissolved; 4 ml of the S precursor was injected into the ZnCd precursor for 10 minutes. After cooling to room temperature, the quantum dots were precipitated with acetone and then dispersed in n-hexane.

[0052] (3) MUA-modified zinc cadmium sulfate quantum dots

[0053] 20 mg of 11-mercaptoundecanoic acid (MUA) was placed in a reaction vessel, 15 ml of methanol (11.85 g) was added, and the pH was adjusted to greater than 10 with tetramethylammonium hydroxide pentahydrate. 20 mg of zinc cadmium sulfate quantum dots (ZnCdSQDs) were dispersed in the mixture under dark conditions, and the vessel was placed under N 2 The mixture was heated under reflux at 60°C overnight. The quantum dots were precipitated with ethyl acetate and ether, washed with acetone and dispersed in water, and were recorded as MUA-ZnCdS QDs.

[0054] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica (10% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst

[0055] 10 mg of zinc cadmium sulfate quantum dots (MUA-ZnCdS QDs) and 90 mg of mesoporous silica (mesop-SiO 2 ) were dispersed in 10 ml of deionized water and stirred for 24 hours in a dark environment to obtain 10% MUA-ZnCdSQDs / mesoporous silica. 2 ) composite photocatalyst.

[0056] (5) 10% MUA-ZnCdS QDs / mesoporous silica 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 experiment.

[0057] 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was passed through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0058] Depend on Figure 1 The specific surface area is calculated to be 225m 2 g -1,Depend on Figure 3 The measured CO production rate is 358.3 μmol g -1 h -1 .

[0059] Example 3

[0060] A kind of zinc cadmium sulfate quantum dots / mesoporous silica (18% MUA-ZnCdS QDs / mesop-SiO 2 ) The method for preparing the composite photocatalyst comprises the following steps:

[0061] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0062] 0.64 g of hexadecyltrimethylammonium bromide (CTAB), 12.0 mL of deionized water and 15.0 mL of butyraldehyde were mixed in a sealed bottle and stirred at 27°C for 5 min. 6.0 mL of ammonia (25-28 wt%) was quickly added and stirred for 30 min. Then 2.8 mL of tetraethyl silicate (TEOS) was added and stirred at 27°C for 24 h. The product was filtered, washed, dried at 100°C for 12 h, and finally calcined in air at 550°C for 6 h.

[0063] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0064] First, 0.51 g of sulfur powder was added to 16 ml of octadecene (ODE) under N 2 The precursor was prepared by heating to 150°C until dissolved; then, 0.256 g of cadmium oxide (CdO) and 0.368 g of zinc acetate (Zn(OAc) 2 ) was added to a mixture of 13 ml of octadecene (ODE) and 6 ml of oleic acid (OA), and then heated to N 2 The precursor was heated to 300 °C until dissolved. 4 ml of S precursor was injected into the ZnCd precursor for 10 min. After cooling to room temperature, the quantum dots were precipitated with acetone and then dispersed in n-hexane.

[0065] (3) MUA-modified zinc cadmium sulfate quantum dots

[0066] 20 mg of 11-mercaptoundecanoic acid (MUA) was placed in a reaction vessel, 15 ml of methanol (11.85 g) was added, and the pH was adjusted to greater than 10 with tetramethylammonium hydroxide pentahydrate. 20 mg of zinc cadmium sulfate quantum dots (ZnCdSQDs) were dispersed in the mixture under dark conditions, and the vessel was placed under N 2 The mixture was heated under reflux at 60°C overnight. The quantum dots were precipitated with ethyl acetate and ether, washed with acetone and dispersed in water, and were recorded as MUA-ZnCdS QDs.

[0067] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica (18% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst

[0068] 18 mg of zinc cadmium sulfate quantum dots (MUA-ZnCdS QDs) and 82 mg of mesoporous silica (mesop-SiO 2 ) were dispersed in 10 ml of deionized water and stirred for 24 hours in a dark environment to obtain cadmium sulfur zinc quantum dots / mesoporous silica (18% MUA-ZnCdSQDs / mesop-SiO 2 ) composite photocatalyst.

[0069] (5) For zinc cadmium sulfate quantum dots / mesoporous silica (18% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 experiment.

[0070] 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was passed through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0071] Depend on Figure 1 The specific surface area calculated from c is 222.1 m 2 g -1 ,Depend on Figure 3 The measured CO production rate is 545.3 μmol g -1 h -1 .

[0072] Example 4

[0073] A kind of zinc cadmium sulfate quantum dots / mesoporous silica (23% MUA-ZnCdS QDs / mesop-SiO 2 ) The method for preparing the composite photocatalyst comprises the following steps:

[0074] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0075] 0.64 g of hexadecyltrimethylammonium bromide (CTAB), 12.0 mL of deionized water and 15.0 mL of butyraldehyde were mixed in a sealed bottle and stirred at 27°C for 5 min. 6.0 mL of ammonia (25-28 wt%) was quickly added and stirred for 30 min. Then 2.8 mL of tetraethyl silicate (TEOS) was added and stirred at 27°C for 24 h. The product was filtered, washed, dried at 100°C for 12 h, and finally calcined in air at 550°C for 6 h.

[0076] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0077] First, 0.51 g of sulfur powder was added to 16 ml of octadecene (ODE) under N 2 The precursor was prepared by heating to 150°C until dissolved; then, 0.256 g of cadmium oxide (CdO) and 0.368 g of zinc acetate (Zn(OAc) 2 ) was added to a mixture of 13 ml of octadecene (ODE) and 6 ml of oleic acid (OA), and then heated to N 2 The precursor was heated to 300 °C until dissolved. 4 ml of S precursor was injected into the ZnCd precursor for 10 min. After cooling to room temperature, the quantum dots were precipitated with acetone and then dispersed in n-hexane.

[0078] (3) MUA-modified zinc cadmium sulfate quantum dots

[0079] 20 mg of 11-mercaptoundecanoic acid (MUA) was placed in a reaction vessel, 15 ml of methanol (11.85 g) was added, and the pH was adjusted to greater than 10 with tetramethylammonium hydroxide pentahydrate. 20 mg of zinc cadmium sulfate quantum dots (ZnCdSQDs) were dispersed in the mixture under dark conditions, and the vessel was placed under N 2 The mixture was heated under reflux at 60°C overnight. The quantum dots were precipitated with ethyl acetate and ether, washed with acetone and dispersed in water, and were recorded as MUA-ZnCdS QDs.

[0080] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica (23% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst

[0081] 23 mg of zinc cadmium sulfate quantum dots (MUA-ZnCdS QDs) and 77 mg of mesoporous silica (mesop-SiO 2 ) were dispersed in 10 ml of deionized water and stirred for 24 hours in a dark environment to obtain cadmium sulfur zinc quantum dots / mesoporous silica (23% MUA-ZnCdSQDs / mesop-SiO 2 ) composite photocatalyst.

[0082] (5) For zinc cadmium sulfate quantum dots / mesoporous silica (23% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 experiment.

[0083] 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was passed through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0084] Depend on Figure 1 The specific surface area is calculated to be 201.8 m 2 g -1 ,Depend on Figure 3 The measured CO production rate is 723.9 μmol g -1 h -1 .

[0085] Example 5

[0086] A kind of zinc cadmium sulfate quantum dots / mesoporous silica (37% MUA-ZnCdS QDs / mesop-SiO 2 ) The method for preparing the composite photocatalyst comprises the following steps:

[0087] (1) Preparation of mesoporous silica (mesop-SiO 2 )

[0088] 0.64 g of hexadecyltrimethylammonium bromide (CTAB), 12.0 mL of deionized water and 15.0 mL of butyraldehyde were mixed in a sealed bottle and stirred at 27°C for 5 min. 6.0 mL of ammonia (25-28 wt%) was quickly added and stirred for 30 min. Then 2.8 mL of tetraethyl silicate (TEOS) was added and stirred at 27°C for 24 h. The product was filtered, washed, dried at 100°C for 12 h, and finally calcined in air at 550°C for 6 h.

[0089] (2) Preparation of zinc cadmium sulfur quantum dots (ZnCdS QDs)

[0090] First, 0.51 g of sulfur powder was added to 16 ml of octadecene (ODE) under N 2 Then, 0.256 g of cadmium oxide (CdO) and 0.368 g of zinc acetate (Zn(OAc) 2 ) was added to a mixture of 13 ml of octadecene (ODE) and 6 ml of oleic acid (OA), and then heated to N2 The precursor was heated to 300 °C until dissolved. 4 ml of S precursor was injected into the ZnCd precursor for 10 min. After cooling to room temperature, the quantum dots were precipitated with acetone and then dispersed in n-hexane.

[0091] (3) MUA-modified zinc cadmium sulfate quantum dots

[0092] 20 mg of 11-mercaptoundecanoic acid (MUA) was placed in a reaction vessel, 15 ml of methanol (11.85 g) was added, and the pH was adjusted to greater than 10 with tetramethylammonium hydroxide pentahydrate. 20 mg of zinc cadmium sulfate quantum dots (ZnCdSQDs) were dispersed in the mixture under dark conditions, and the vessel was placed under N 2 The mixture was heated under reflux at 60°C overnight. The quantum dots were precipitated with ethyl acetate and ether, washed with acetone and dispersed in water, and were recorded as MUA-ZnCdS QDs.

[0093] (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica (37% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst

[0094] 37 mg of zinc cadmium sulfate quantum dots (MUA-ZnCdS QDs) and 63 mg of mesoporous silica (mesop-SiO 2 ) were dispersed in 10 ml of deionized water and stirred for 24 hours in a dark environment to obtain 37% MUA-ZnCdSQDs / mesoporous silica. 2 ) composite photocatalyst.

[0095] (5) For zinc cadmium sulfate quantum dots / mesoporous silica (37% MUA-ZnCdS QDs / mesop-SiO 2 ) Composite photocatalyst for photocatalytic reduction of CO 2 experiment.

[0096] 10 mg of catalyst was dispersed in 3 ml of deionized water. The resulting mixture was dropped onto a quartz glass and then dried at 60 °C. The dried catalyst was placed in a quartz reactor containing 1 mL of water. Carbon dioxide was then introduced into the reactor for 30 min to completely remove the air. During the reaction, a xenon lamp was passed through a quartz window (22.1 cm 2 ) illuminates the catalyst sample.

[0097] Depend on Figure 1 The specific surface area can be calculated to be 50.7 m 2 g -1 .

[0098] Transmission image Figure 2As shown, the morphology of zinc cadmium sulfur quantum dots is particles with a diameter of 8nm, which are evenly dispersed and uniform in size. The morphology of mesoporous silica is nanospheres with a diameter of about 120nm and a clear mesoporous structure on the surface. The morphology of the zinc cadmium sulfur quantum dots / mesoporous silica composite photocatalyst shows that the mesoporous silica is evenly covered with quantum dots, indicating that the zinc cadmium sulfur quantum dots / mesoporous silica composite photocatalyst was successfully prepared.

[0099] Depend on Figure 3 The measured CO production rate is 898.6 μmol g -1 h -1 .

[0100] The results of the cycle test are as follows Figure 4 As shown in Figure 2, after 20 h of circulation, the CO production rate can reach 816.7 μmol g -1 h -1 .

Claims

1. A method for preparing a zinc cadmium sulfate quantum dot / mesoporous silica composite photocatalyst, characterized in that: Here are the steps: (1) Preparation of mesoporous silica mesop-SiO2: Dissolve hexadecyltrimethylammonium bromide (CTAB) and butyraldehyde in water and pour into a sealed bottle and stir for the first time at room temperature, quickly add ammonia water, stir for the second time, then add tetraethyl silicate (TEOS), stir for the third time at room temperature, centrifuge and dry the product, and finally calcine in air atmosphere; (2) Preparation of zinc cadmium sulfur quantum dots ZnCdS QDs: First, sulfur powder is added to octadecene ODE and heated under N2 until dissolved to prepare S precursor; then, cadmium oxide CdO and zinc acetate Zn(OAc)2 are added to a mixture of octadecene ODE and oleic acid OA and heated under N2 until dissolved to prepare ZnCd precursor; finally, S precursor is injected into ZnCd precursor and cooled to room temperature, and the obtained sulfur cadmium zinc quantum dots are precipitated with acetone and then dispersed in n-hexane; (3) MUA-modified zinc cadmium sulfate quantum dots Dissolve 11-mercaptoundecanoic acid MUA in methanol, and adjust the pH of the solution to 9-12 with tetramethylammonium hydroxide pentahydrate to obtain a MUA mixed solution; In dark conditions, the zinc cadmium sulfur quantum dots ZnCdS QDs obtained in step (2) are dispersed in the MUA mixed solution, and the container is placed under N2 flow. The mixture is heated under reflux overnight, precipitated with ethyl acetate and diethyl ether, washed with acetone and dispersed in water, and recorded as MUA-ZnCdS QDs; (4) Preparation of zinc cadmium sulfate quantum dots / mesoporous silica composite photocatalyst The MUA-ZnCdS QDs obtained in step (3) and the mesoporous silica mesop-SiO2 obtained in step (1) are dispersed in deionized water, stirred for 12-24 hours in the dark, and a zinc cadmium sulfate quantum dot / mesoporous silica composite photocatalyst is obtained, which is recorded as MUA-ZnCdS QDs / mesop-SiO2.

2. The preparation method according to claim 1, characterized in that In step (1), the dosage ratio of hexadecyltrimethylammonium bromide, butyraldehyde, ammonia water and tetraethyl silicate is 0.64g:15.0mL:6.0mL:2.8mL; wherein the concentration of ammonia water is 25-28wt%.

3. The preparation method according to claim 1, characterized in that: In step (1), the first stirring time is 5-10 min, the second stirring time is 30-60 min, the third stirring time is 12-24 h, the calcination temperature is 550° C., and the calcination time is 6 h.

4. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of sulfur powder, CdO and Zn(OAc)2 is 2:1:1; in the mixture of octadecene ODE and oleic acid OA, the volume ratio of ODE:OA is 13:

6.

5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of MUA and ZnCdS QDs is 1:

1.

6. The preparation method according to claim 1, characterized in that: In step (3), the reflux temperature is 60-80°C.

7. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of MUA-ZnCdS QDs to mesoporous silica mesop-SiO2 is 1:1.7-19.

8. The preparation method according to claim 1, characterized in that: In step (4), the stirring time in the dark is 12-24 hours.

9. Use of the sulfur cadmium zinc quantum dot / mesoporous silica composite photocatalyst prepared by the method according to any one of claims 1 to 8 for photocatalytic reduction of CO2 to CO.

Citation Information

Patent Citations

  • Lead-free double perovskite and silicon dioxide submicrocapsule core-shell structure and application thereof in photocatalytic carbon dioxide reduction

    CN115888770A

  • Preparation method of mesoporous oxide coated quantum dots, quantum dot photoresist and preparation method thereof, and luminescent device

    CN118360048A

  • Hollow macroporous-microporous molecular sieve encapsulated nano cadmium zinc sulfide photocatalyst and preparation method thereof

    CN118719160A